The Effect of Combination Foot Massage and Active Range of Motion (ROM) on Foot Sensitivity among Patients with Type 2 Diabetic Mellitus - Agastiya, I Made Cahyadi; Romani, Ni Ketut; Artana, I Made (Babali Publisher, 2025)
Introduction: T2DM can increase morbidity and mortality. Almost half of T2DM patients have impaired foot sensitivity. This increases the risk of diabetic foot ulcers, causing the patient to not feel any injuries to the legs, even to amputation. Therefore, handling the proper treatment to prevent these complications is necessary, one of which is using foot massage and active ROM. This study aimed to determine the effect of the combination of foot massage and active ROM on foot sensitivity among T2DM patients at Mangusada Hospital. Methods: This study was carried out in the Kecak Room of Mangusada Hospital, involving 30 T2DM patients. This study uses a pre-experiment design with a one-group pretest-posttest design. The instrument used to assess foot sensitivity among T2DM patients was a 10-g monofilament applied at five points on each patient's right and left soles. The normality test results showed that the data was not normally distributed, so the Wilcoxon Signed Rank Test was used to analyze the difference in foot sensitivity of T2DM patients before and after the intervention with a significance level (α<0.05). Results: The results showed that median foot sensitivity scores improved from 7 to 8. Before the intervention, most foot sensitivity scores were 7, and after the intervention, they were 8. It can be concluded that a combination of foot massage and active ROM affected foot sensitivity among T2DM patients at Mangusada Hospital. Conclusion: Future studies should incorporate a control group and randomization to enhance validity.